2020
DOI: 10.3390/ijms21176235
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Evidence Involved in the Role of Endocannabinoid Signalling in Parkinson’s Disease: A Perspective on Associated Therapeutic Interventions

Abstract: Current pharmacotherapy of Parkinson’s disease (PD) is symptomatic and palliative, with levodopa/carbidopa therapy remaining the prime treatment, and nevertheless, being unable to modulate the progression of the neurodegeneration. No available treatment for PD can enhance the patient’s life-quality by regressing this diseased state. Various studies have encouraged the enrichment of treatment possibilities by discovering the association of the effects of the endocannabinoid system (ECS) in PD. These reviews del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 204 publications
(270 reference statements)
0
20
0
Order By: Relevance
“…With multifaceted etiologies and about two percent prevalence in the older populations (mainly >60 age), PD is one of the most common, long-term, age-related ND, which has been causing significant burden and disability in the quality of life [ 80 ]. It is proposed that the progression and pathogenesis of PD is associated with prominent characteristic i.e., α-synuclein inclusions in the Lewy bodies in affected areas of brain [ 81 ].…”
Section: Involvement Of Mmps In Ndsmentioning
confidence: 99%
See 1 more Smart Citation
“…With multifaceted etiologies and about two percent prevalence in the older populations (mainly >60 age), PD is one of the most common, long-term, age-related ND, which has been causing significant burden and disability in the quality of life [ 80 ]. It is proposed that the progression and pathogenesis of PD is associated with prominent characteristic i.e., α-synuclein inclusions in the Lewy bodies in affected areas of brain [ 81 ].…”
Section: Involvement Of Mmps In Ndsmentioning
confidence: 99%
“…Thus, the validation of MMP blockers serve as a therapeutic opportunity, because BBB perturbations may also occur in neurodegeneration. Hence, MMPs and associated mechanisms may also be potential targets for neurodegenerative disorders [79] With multifaceted etiologies and about two percent prevalence in the older populations (mainly >60 age), PD is one of the most common, long-term, age-related ND, which has been causing significant burden and disability in the quality of life [80]. It is proposed that the progression and pathogenesis of PD is associated with prominent characteristic i.e., α-synuclein inclusions in the Lewy bodies in affected areas of brain [81].…”
Section: The Links Between Mmps and Aquaporin-4mentioning
confidence: 99%
“…The main hemp phytochemicals that are synthesized in trichomes that cover the leaves, branches, and stems of the plant belong to the following classes: cannabinoids (more than 100), polyphenols, flavonoids, terpenoids (which give the smell of the crop), amides, amines, carbohydrates, fatty acids, and esters, with many of them having medical uses [ 8 ], alone or in diverse preparations. The results of several studies have demonstrated the involvement of phytocannabinoids in several central and peripheral pathophysiological mechanisms, namely: food intake (modulate hunger/satiety), multiple sclerosis, inflammation, pain [ 9 ], spasticity, colitis, nausea and vomiting, anorexia, Tourette syndrome, sleep disorders, anxiety, epilepsy, Alzheimer’s disease, and Parkinson’s disease [ 2 , 10 , 11 ]. Therefore, a strict pathway to obtain authorization for a potential medicinal product containing hemp preparations, which have little or no psychoactive effect because they contain low levels of Δ 9 -tetrahydrocannabinol (Δ 9 -THC), is required, and has been mentioned in a recent report from the European Monitoring Centre for Drugs and Drug Addiction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This unique function of eCBs suggested their investigation as therapeutic targets for human diseases affecting central nervous system (CNS) [13]. Indeed, the eCB system dysregulation in the CNS has been increasingly implicated in the physiopathology of neurodegenerative and neuropsychiatric disorders, such as AD [18], Parkinson's disease [34], Huntington's disease [35], multiple sclerosis [36] schizophrenia [37] and anxiety disorders [38]. CB 1 and CB 2 are differently expressed throughout human body and their distribution correlated with their specific physiological roles.…”
Section: The Ecb System and The Endocannabinoidomementioning
confidence: 99%